Pattern of contributing behaviors and their determinants among people living with HIV in Iran: A 30-year nationwide study - Gheibi, Zahra; Fararouei, Mohammad; Afrashteh, Sima; Akbari, Mojtaba; Afsar Kazerooni, Parvin; Shokoohi, Mostafa (Frontiers in Public Health, 2023)
Introduction A major shift in the routes of HIV transmission seams to be taking place in Iran. Our study aimed to investigate the 30-year trend of major HIV related behaviors in Iran. Methods The national HIV/AIDS registry database (from September 1986 to July 2016 with data on 32,168 people newly diagnosed with HIV) was used to study the 30 years trend and demographic determinants of major HIV related behaviors. Results The highest rate of drug injection (DI) among people living with HIV (PLHIV) was reported during 1996 to 1999 (p-for trend < 0.001) while the highest rate of sexual activity by minorities or hard to reach groups was during 2004 to 2011 (p-for trend < 0.001). Among males, drug injection was directly associated with being single (ORsingle/married = 1.34), being unemployed (ORunemployed/employed = 1.94) and having lower level of education (OR<highschool/≥highschool = 2.21). Regarding females, drug injection was associated with being housewife (ORhousewife/employed = 1.35) and lower level of education (OR<highschool/≥highschool = 1.85). In females, condomless sexual contact was more common among those younger (OR20−29/<20 = 6.15), and married (ORmarried/single = 7.76). However, among males those being single (ORmarried/single = 0.82), being more educated (OR≥highschool/<highschool = 1.24), and being unemployed (ORunemployed/employed = 1.53) reported more sexual activity by minoritised or hard to reach groups. Discussion The pattern of major HIV related behaviors among Iranian males and females have been rapidly changing and people living with HIV (PLHIV) are being diagnosed at a younger age. Health education to younger individuals is an essential HIV controlling strategy among Iranian population. Implementation of surveys in hidden and hard-to-reach populations is also recommended.